Anaesthetic Management Of A Case Receiving Replacement Treatment For Adrenal İnsufficiency And Hypothyroidism (Annals of Medical Research, 2021)
None
Keywords: Anaesthetic Management: Multiple Endocrine Neoplasia II (MEN II), Adrenal İnsufficiency, Hypothyroidism, Hormone Replacement.